Influence Determination of Social Responsibility to the Productivity Enterprise Activity Level - Sergii Kavun; Ganna Zhosan (Economies, 2016)
The purpose of this paper is to develop a scientific and methodical approach for determination of the comprehensive social responsibility indicator in this paper based on estimation of influence degree for the economical, ecological, social and labour, standard and legal components. There is allowance for determining of some level of enterprise social responsibility. In addition, there is a basis for development some ways of their increasing. The essence of the used approach is clotting of the individual indicators set to four intermediate indicators of the economic, ecological, social and labor, standard and legal components, which can be boiled down to the generalizing activity productivity indicator based on the matrix and range approach. An economical and mathematical model of the social responsibility influence level to the enterprise activity productivity level, which is based on enterprise propose harmonization with the participants’ interests, was being built. The paper proposes the mathematical model, which allows detecting a necessary time period for enterprise activity productivity ensuring due to social responsibility implementation.